2017
DOI: 10.1007/s11749-017-0565-z
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrap- and permutation-based inference for the Mann–Whitney effect for right-censored and tied data

Abstract: The Mann-Whitney effect is an intuitive measure for discriminating two survival distributions.Here we analyze various inference techniques for this parameter in a two-sample survival setting with independent right-censoring, where the survival times are even allowed to be discretely distributed. This allows for ties in the data and requires the introduction of normalized versions of Kaplan-Meier estimators from which adequate point estimates are deduced. Asymptotically exact inference procedures based on stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…On the other hand, Akritas (1986) has verified that Efron's bootstrap for right-censored data (Efron, 1981) still works in the presence of ties. The planned future paper may also be considered an extension of the article by Dobler and Pauly (2017) to the multi-sample and multivariate case.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Akritas (1986) has verified that Efron's bootstrap for right-censored data (Efron, 1981) still works in the presence of ties. The planned future paper may also be considered an extension of the article by Dobler and Pauly (2017) to the multi-sample and multivariate case.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The second equality follows from the functional delta-method applied to the integral functionals φ i ; cf. Dobler and Pauly (2017) for the two-sample case. In this asymptotic expansion, the now proposed wild bootstrap tries to estimate each involved residual ε jk (x) = c(x − X jk ) − F j (x), k = 1, .…”
Section: Asymptotic Properties and Resampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al 13 indicated that the conducted statistics based on the area difference between two curves are unstable with small sample sizes; thus, we proposed a permutation procedure to avoid this problem. We named this method the permutation test 14 (Perm). First, according to ABC test, we can obtain the Z ABC statistics.…”
Section: Methodsmentioning
confidence: 99%
“…As this can be hard to verify or simply wrong, some alternatives to hazard ratios as effect sizes are desired that provide “ clinically meaningful outcomes for (…) patients ” and for “ discussing the value of clinical trials with patients ”. 7 Proposed alternatives cover average hazard ratios, 8,9 concordance and Mann–Whitney effects, 1012 the (restricted) mean survival, 13,14 or median survival times (MSTs). 1517…”
Section: Introductionmentioning
confidence: 99%